Highlights of the 6th World Congress in Paediatric Cardiology and Cardiac Surgery. (May 2013) - Hayes, Nicholas; Chubb, Henry; Narayan, Srinivas; Qureshi, Shakeel
The 6th World Congress in Paediatric Cardiology and Cardiac Surgery took place in Cape Town, South Africa, in February 2013. The congress is the largest meeting in the field of congenital and paediatric heart disease and attracts a global audience of specialists with the aim of sharing the latest multidisciplinary developments in research and clinical practice. The congress was commended as a huge success and this article aims to give a general flavor of the diverse meeting through detailing a few specific highlights from the various tracks.